Delayed Diagnosis of Glioblastoma due to Recent Ruptured Aneurysm. A Case Report. - Ronchetti, Gabriele; Giussani, Carlo (Journal of Brain And Spinal Cancer, 2017)
Rupture of an intracranial aneurysm may cover for a long time clinical and radiological signs of a coexistent tumor. We report the delayed diagnosis of glioblastoma in a 65-years old female with recent history of subarachnoid hemorrhage. In the literature are described few similar cases: we briefly discuss the management in the rare occurrence of a double neurosurgical disease.
Keywords: Glioblastoma; cerebral tumor; diagnosis; subarachnoid hemorrhage; aneurysm; hydrocephalus.